Testing for Prudence and Skewness Seeking - Ebert, Sebastian; Wiesen, Daniel (Management Science, 2011)
Numerous theoretical predictions such as precautionary saving or preventive behavior have been derived for prudent decision makers. Further, prudence can be characterized as downside risk aversion and plays a key role in preference for skewness. We use a simple experimental method to test for prudence and skewness preference in the laboratory and compare the two. To this end, we introduce a novel graphical representation of compound lotteries that is easily accessible to subjects and test it for robustness, using a factorial design. Prudence is observed on the aggregate and individual level. We find that prudence does not boil down to skewness seeking. We further provide some theoretical explanations for this result. This paper was accepted by Peter Wakker, decision analysis.